Pengaruh Keterlibatan Kerja Dan Semangat Kerja Terhadap Prestasi Kerja Pegawai Selama Pandemi Pada Kantor DAMRI Kota Sorong (Jurnal Manajemen Kreatif dan Inovasi, 2023)
This study aims to analyze the effect of work involvement and morale on employee performance at the Sorong DAMRI Office. This study uses descriptive quantitative research methods and correlations. Data collection techniques using questionnaires and interviews with all employees of the Sorong DAMRI Office as many as 30 respondents using the Saturated Sampling Technique. This study uses the SPSS Version 25 application program for windows, the results of this study indicate that the variables of work involvement and morale on employee performance have a positive and significant effect.